Undrained shear strength of soft clay reinforced with encapsulated polypropylene (PP) column - Alvin Ngieng, Wen Hong (2019)
Granular column is gaining popularity in current market as many researches had proven that it does enhance the strength of soft soil in certain degree. Also, abundant plastic had caused many environmental issues to the earth. Therefore, the main objective of this study is to investigate the effectiveness of encapsulated polypropylene (PP) column in enhancing the undrained shear strength of kaolin (soft clay). The usage of PP in treating problematic soil is a more sustainable and cost-effective alternative compared to other materials. In the construction site, installation of granular column can be done by using vibro replacement method. Firstly, several geotechnical tests to determine the properties of materials were done and the result was clearly discussed. The shear strength of treated kaolin sample was examined by using Unconfined Compression Test (UCT). There are 7 batches of soil sample in total which included a control sample, 3 batches of 14mm and 3 batches of 20mm diameter PP column. Different diameters of PP column were examined with 60 mm, 80 mm and 100 mm height respectively. The soil sample itself is 50mm in diameter and 100mm in height. The shear strength improvement of kaolin is 33.82%, 46.51% and 49.88% when it is implanted with PP column that is having 7.84 area replacement ratio and 0.6, 0.8 and 1.0 penetration ratio. Meanwhile, the soft soil treated by using 16.00 area replacement ratio with 0.6, 0.8 and 1.0 penetration ratio has a shear strength increment of 25.22%, 33.39% and 37.59% respectively. From the result, the Hc/Dc ratio was found to be within 4-8 which is same as the one recommended by previous researchers. In short, the shear strength improvement of the kaolin clay is very depending on the parameter of the PP column that used to reinforce the sample.